Overexpression of 5-methylcytosine DNA glycosylase in human embryonic kidney cells EcR293 demethylates the promoter of a hormone-regulated reporter gene - Zhu, Bing (The National Academy of Sciences, 2001)
We have shown that the DNA demethylation complex isolated from chicken embryos has a G⋅T mismatch DNA glycosylase that also possesses 5-methylcytosine DNA glycosylase (5-MCDG) activity. Herein we show that human embryonic kidney cells stably transfected with 5-MCDG cDNA linked to a cytomegalovirus promoter overexpress 5-MCDG. A 15- to 20-fold overexpression of 5-MCDG results in the specific demethylation of a stably integrated ecdysone-retinoic acid responsive enhancer-promoter linked to a β-galactosidase reporter gene. Demethylation occurs in the absence of the ligand ponasterone A (an analogue of ecdysone). The state of methylation of the transgene was investigated by Southern blot analysis and by the bisulfite genomic sequencing reaction. Demethylation occurs downstream of the hormone response elements. No genome-wide demethylation was observed. The expression of an inactive mutant of 5-MCDG or the empty vector does not elicit any demethylation of the promoter-enhancer of the reporter gene. An increase in 5-MCDG activity does not influence the activity of DNA methyltransferase(s) when tested in vitro with a hemimethylated substrate. There is no change in the transgene copy number during selection of the clones with antibiotics. Immunoprecipitation combined with Western blot analysis showed that an antibody directed against 5-MCDG precipitates a complex containing the retinoid X receptor α. The association between retinoid receptor and 5-MCDG is not ligand dependent. These results suggest that a complex of the hormone receptor with 5-MCDG may target demethylation of the transgene in this system.